PEMAKAIAN HYDROGEN COOLING SYSTEM PADA GENERATOR UNIT 1 PLTU TAMBAK LOROK PT INDONESIA POWER UBP SEMARANG - Winardi, Bambang (Transmisi, 2007)
Synchronous generator is an ac generator which performs in constant frequency. Synchronous generator in a power station, e.g. Unit I PLTU Tambak Lorok, PT Indonesia Power, Generation Business Unit (UBP) Semarang has to supply the load in long period without rests. Regarding to perform this operation, generator will suffer a heat which comes from energyd issipationa s a result of resistanceo frotor and statorw indings. The heat is very disadvantageoufso r which it can causet he decreasingo fgcnerator performance.I fthe amount of hcat is too cxcessive, it can causc the damage of generator winding. For this reatnn, a cooling system is required in the gcnerator for avoiding any cases previously mentioned. One ofcooling systemsi s that usesh ydrogeng as.T he advantageo fthe hydrogeng as is that it can bind any heat anywhere it flows. Â  Kata kunci: Cooler System,g eneratorh, ydrogen